The atonement : a brief discussion - Hay, Thomas Alexander (Rhodes University, Faculty of Divinity, Department of Divinity, 1958)
This first section endeavours briefly to set out the problem, seeing it ln its proper context against the need it fulfils and its historical setting. It attempts to show something of the nature of sin and the need which sin creates; and asks the question Why Atonement? This question can only be answered by an appreciation of the meaning and power of sinfulness. Atonement is necessarily from God's side, and it is costly to God. An important factor in this section is the attempt to see the wholeness of Christ's work; to set the atonement in its true context within the life of Christ. An attempt is made to relate the atonement to the incarnation, The Word made flesh and dwelling among us; to the resurrection, which is not to be misunderstood as a mere evidential appendage to the cross, but to be seen as an essential factor in the salvation of men; and also to the ascension, to the problem of time and eternity, in that while Christ's work was once-for-all, it is nevertheless continued - it was in history, but is not bound within history. When this conception of the unity of Christ's work is grasped then we can turn to a consideration of the cross, always regarded by Faith as the very centre of the atonement. A brief survey is made of the Biblical teaching concerning salvation and the cross; and the centrality of the cross is interpreted sacrificially. Summary, p. x-xi.
Keywords: Atonement; Satisfaction for sin